2016
DOI: 10.1088/1475-7516/2016/10/009
|View full text |Cite
|
Sign up to set email alerts
|

Inverse construction of the ΛLTB model from a distance-redshift relation

Abstract: Spherically symmetric dust universe models with a positive cosmological constant Λ, known as Λ-Lemaître-Tolman-Bondi(ΛLTB) models, are considered. We report a method to construct the ΛLTB model from a given distance-redshift relation observed at the symmetry center. The spherical inhomogeneity is assumed to be composed of growing modes. We derive a set of ordinary differential equations for three functions of the redshift, which specify the spherical inhomogeneity. Once a distanceredshift relation is given, wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In the case of ΛLTB models, as is shown in ref. [15], once the value of the cosmological constant is fixed and the angular diameter distance is specified as a function of the redshift, we can uniquely determine the ΛLTB model. Therefore, the parameters to specify a ΛLTB model are equivalent to the parameters contained in the distance redshift relation beside the value of the cosmological constant.…”
Section: Jcap03(2018)033mentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of ΛLTB models, as is shown in ref. [15], once the value of the cosmological constant is fixed and the angular diameter distance is specified as a function of the redshift, we can uniquely determine the ΛLTB model. Therefore, the parameters to specify a ΛLTB model are equivalent to the parameters contained in the distance redshift relation beside the value of the cosmological constant.…”
Section: Jcap03(2018)033mentioning
confidence: 99%
“…In section 2, we briefly review the inverse construction method reported in ref. [15] and how to construct a universe model in the late time domain. The method to calculate the CMB angular power spectrum and the parameter set for the MCMC analysis is summarized in section 3.…”
Section: Jcap03(2018)033mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, calibrating SN Ia absolute magnitude with the use of Cepheid variable stars and fixing the local distance-redshift relation (at z ≤ 0.15) leads to a remarkable cosmology-independent measurement of H 0 (Riess et al 2005(Riess et al , 2009(Riess et al , 2011(Riess et al , 2016(Riess et al , 2018. Different calibration techniques consider the usage of strong gravitational lensing (Taubenberger et al 2019), tip of the red giant branch (Beaton et al 2016;Freedman et al 2019), HII regions (Fernández Arenas et al 2018), etc. Due to the strong correlation of cosmic expansion dynamics and H 0 value, the model-independent local estimates remain crucial for the study of late-time cosmic evolution (see also Tutusaus et al (2019); Haridasu et al (2018b)).…”
Section: Introductionmentioning
confidence: 99%
“…isotropic inhomogeneities may cause systematic errors on the amount of dark energy and its equation of state. Some authors studied systematic errors due to isotropic inhomogeneities and have evaluated the magnitude of them [14][15][16][17][18][19][20][21][22][23][24]. However, nobody has not shown how to remove the systematic errors caused by isotropic inhomogeneities.…”
Section: Introductionmentioning
confidence: 99%